Consumers’ Attitudes Toward Domestic Leisure Tourism: The Case of Bulgaria - Desislava Varadzhakova; Alexander Naydenov (Tourism and Hospitality)
The present paper aims to analyze consumers’ attitudes to domestic leisure tourism, considering essential factors that affect consumer travel choices and experiences. The focus is on the attitudes to the main advantages and disadvantages of domestic leisure tourism in Bulgaria. The research is based on the outcomes of a nationally representative survey among 1003 respondents aged over 18. The results are interpreted using the Fishbein multi-attribute model. The results reveal that the customers’ attitudes toward the advantages of the Bulgarian winter (ski) and summer (sea) domestic leisure tourism are relatively higher compared to the midpoint of the interval and to their highest point. Although the score for summer domestic leisure tourism is slightly lower than that of winter tourism, Bulgarian consumers appear to be more dissatisfied with the advantages of summer (sea) domestic leisure tourism. The dissatisfaction is not only greater compared to the midpoint of the scale but also in comparison to the disadvantages associated with winter domestic leisure tourism. Overall, Bulgarian consumers are more attracted to the positive aspects of domestic winter leisure tourism and more concerned about the negative aspects of summer tourism.